La fijación de pensiones alimenticias provisionales en el trámite de divorcio contencioso y su incidencia en el desarrollo integral del menor en los juicios emitidos por la unidad judicial familia, mujer niñez y adolescencia con sede en el cantón Riobamba, durante el período de mayo a diciembre del 2016. - Cadena Cocha, Luis Felipe (2018)
The investigation deals with the fixing of provisional food pension in the controversial divorce process, with the purpose of establishing the incidence in the integral development of the minor in the judgments issued by the Judicial Unit Family, Woman, Childhood and Adolescence with headquarters in the canton Riobamba, during the period from May to December 2016; in this way we will see if it affects or not the integral development of the minor; also the treatment to this fixation of provisional pensions of food, its fulfillment and the ones in charge to give the mentioned pension. It will be analyzed about the institution of marriage, the grounds for ending the relationship of the marriage, the contentious divorce trial, the termination of the marriage, the procedure, the fixing of the provisional maintenance of food, the right to food, the holders the right to food, those obliged to provide food, the protection of the child in the right to food, decent subsistence, parental-filial responsibility, everything related to the child and its integral development. The present investigation will be a great contribution and as a source of consultation especially for the students of the Law course of the National University of Chimborazo; also for the judges of the Family, Women, Children and Adolescents Judicial Unit based in the canton of Riobamba, lawyers in the free exercise of the profession and citizenship in general.